Modelo matemático e computacional para robôs espaciais de base livre e múltiplos braços com momento não-conservado - Rodrigues, Gabriel da Silva (Universidade Federal de São Carlos, 2025)
The development of orbital space robotics in recent decades is aimed at meeting the demand for extra-vehicular missions, such as supply, maintenance, inspection, rescue and transport of materials. A space manipulator can be defined by one or more arms attached to a floating base (satellite) designed for operation in orbit. The distinguishing characteristic of these systems is the dynamic coupling between the base and the manipulators. In this work, a mathematical model is proposed for a space robot with multiple arms and a floating base, capable of dealing with external forces and non-zero linear and angular momentum, especially to maximize the fidelity between the model and the robot in detumbling applications. The main objective is to present a mathematical model that is sufficiently detailed in the constructions of vectors and matrices necessary for its implementation, maintaining its functional generality and consistency with the real operation of the manipulator in terms of obedience to the laws of classical mechanics. The work in question addresses gaps in the literature regarding the dynamic model in Cartesian space and the behavior of the robotic system in conditions of interaction with non-cooperative targets, such as inconsistencies in the calculations of non-inertial terms and angular momentum, mapping of forces between joint and task domains through the Generalized Jacobian Matrix and cancellation of momentum in post-impact situations. From simulations, it is clear that the presented formulations are internally consistent in joint and inertial domains. The application of multiple target stabilization tasks, whose formulation is based on the generalization of the spatial Jacobian for multiple arms, presented satisfactory performance, thus assuming a relevant role in future applications involving multiple target detumbling.
Mathematical and computational model for free-floating, multi-arm space robots with non-conserved momentum
Keywords: Robótica espacial; Modelagem dinâmica; Detumbling; Space robotics; Dynamic modeling; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS; 9. Indústria, Inovação e Infraestrutura